THE EFFECT OF PRODUCT QUALITY AND BRAND IMAGE ON PURCHASING DECISIONS AT PT ARINT PREMIUM FITTING GATSU TIMUR DENPASAR - Paramartha, I Nyoman Satya (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Ngurah Rai, 2025)
In making purchasing decisions there are influencing variables such as product quality and brand image. There are concerns and problems encountered related to product quality and brand image in an effort to create purchasing decisions, so it is very appropriate in this study to examine further the influence of product quality and brand image on purchasing decisions at PT. Arint Premium Fitting Gatsu Timur Denpasar. The number of samples was determined by purpusive sampling method as many as 94 consumers of PT. Arint Premium Fitting. Data were analyzed using the classical assumption test, multiple linear regression analysis, multiple correlation analysis, determinant analysis, simultaneous significance test (F-test), and partial significance test (t-test). The results showed that there was a positive and significant effect simultaneously on product quality and brand image on purchasing decisions at PT. Arint Premium Fitting. While partially product quality has a positive and significant effect on purchasing decisions at PT. Arint Premium Fitting. Partially, brand image has a positive and significant effect on purchasing decisions at PT. Arint Premium Fitting